On the Taxonomic Status of Pisidium uejii (Mollusca, Bivalvia) - Korniushin, A.V. (Вестник зоологии, 1999)
Type specimens of Pisidium uejii Mori, 1938 from Japan, deposited in the collection of Senckenbergsmuseum, Frankfurt-am-Main, are studied and the species is shown to belong to the subgenus Odhneripisidium Kuiper. It is the second species of this subgenus known from Japan. Изучены типовые экземпляры Pisidium uejii Mori, 1938 из Японии, хранящиеся в Зснкенбергском музее (Франкфурт-на-Майне). Показана принадлежность вида к подроду Odhneripisidium Kuiper. Это второй вид подрода, обнаруженный в Японии.